Nonlocal eigenvalue problems with indefinite weight - Taarabti, S. (Methods of Functional Analysis and Topology, 2020)
In the present paper, we consider a class of eigenvalue problems driven by a nonlocal integro-differential operator L_K^p(x) with Dirichlet boundary conditions. Under certain assumptions on p and q, we establish that any λ>0 suficiently small is an eigenvalue of the nonhomogeneous nonlocal problem (P_λ). Розглядається клас спектральних задач, пов’язаних із нелокальним інтегро-диференціальним оператором L_K^p(x) із крайовою умовою Дирихле. За певних припущень щодо p і q доведено, що кожне достаньо мале λ>0 є власним значенням неоднорідної нелокальної задачі (P_λ).